Examining the Coping Response to Peer Relational Aggression Victimization - Melissa M. Gomes (Nursing Research and Practice)
Purpose. Relational aggression, rumor spreading, backstabbing, and social isolation, is psychologically damaging for adolescent girls. The purpose of this study was to provide an explanation of victimization response after experiencing peer relational aggression victimization. Methods. Grounded theory techniques were used to gain an understanding of the victimization experience and the coping responses used. Findings. A theory of coping after experiencing peer relational aggression victimization was generated. Girls voiced feelings of hurt and anger after the experience and expressed the following ways of coping as a result: distancing from others, retaliation against the aggressor, discussing their feelings with friends and family, writing their feelings down, and/or confronting the aggressor. Clinical Implications. Nurses should be aware of the phenomenon and asses, for incidences of relational aggression victimization so that they may provide strategies to assist the adolescent and her family with positive coping mechanisms in order to prevent maladaptive responses.